PPARγ: A Novel Molecular Target in Lung Disease. (1st February 2008) - Hart, C. Michael; Roman, Jesse; Reddy, Raju; Sime, Patricia J.
Abstract : Interest in peroxisome proliferator-activated receptors (PPARs) has steadily increased over the past 15 years. The recognition that subclasses of this receptor played critical roles in regulation of metabolism led to the development of synthetic ligands and their widespread application in the treatment of type 2 diabetes. At the same time, emerging evidence demonstrated that the influence of PPARs extends well beyond metabolism and diabetes. A salient example of this can be seen in studies that explore the role of PPARs in lung cell biology. In fact, current literature suggests that PPAR receptors may well represent exciting new targets for treatment in a variety of lung disorders. In an attempt to keep the scientific and medical communities abreast of these developments, a symposium sponsored by the American Federation for Medical Research entitled "PPARγ: A Novel Molecular Target in Lung Disease" was convened on April 29, 2007, at the Experimental Biology Meeting in Washington, DC. During that symposium, 4 speakers reviewed the latest developments in basic and translational research as they relate to specific lung diseases. Jesse Roman, MD, professor and director of the Emory University Division of Pulmonary, Allergy, and Critical Care Medicine, reviewed the role of PPARγ in the pathogenesis of lung cancer and its implications for therapy. Raju Reddy, MD, assistant professor of Medicine at the University of Michigan, presented data regarding the immunomodulatory role of PPARγ in alveolar macrophages. Patricia J. Sime, MD, associate professor of Medicine, Environmental Medicine, and Oncology at the University of Rochester School of Medicine, discussed the antifibrogenic potential of PPARγ ligands in pulmonary fibrosis. Finally, C. Michael Hart, MD, professor of Medicine at Emory University and chief of the Atlanta Veterans Affairs Medical Center Pulmonary Section, reviewed the role of PPARγ in pulmonary vascular disease. This brief introduction to the symposium will provide background information about PPARs to facilitate the general reader's appreciation of the more in-depth and disease-specific discussions that follow.